Computational framework for interactive architecting of complex systems. Issue 3 (17th February 2020) - Guenov, Marin D.; Riaz, Atif; Bile, Yogesh H.; Molina‐Cristobal, Arturo; van Heerden, Albert S.J.
Abstract: Presented is a novel framework for interactive systems architecture definition at early design stages. It incorporates graph‐theoretic data structures, entity relationships, and algorithms that enable the systems architect to operate interactively and simultaneously in different domains. It explicitly captures the "zigzagging" of the functional reasoning process, including not only allocated, but also the derived functions. A prototype software tool, AirCADia Architect, was implemented, which allowed the framework to be demonstrated to and tried hands‐on by practicing aircraft systems architects. The tool enables architects to effectively express their ideas when interactively synthesizing new architectures, while still retaining control over the process. The proposed approach was especially acknowledged as the way forward for rationale capture.